Digital Story Telling Based on Multimodal Elements on EFL Learners’ Speaking Performance - Yuniarti, Yuniarti; Yulian, Ryani (Jurnal Pendidikan Indonesia, 2022)
Educators must adapt the contextual model of teaching with educational technology to improve teaching and learning English quality. Digital storytelling is one of meaningful technology that can enhance students' speaking skills. This study examined the effectiveness of digital storytelling based on multimodal elements on EFL learners' speaking performance. A quasi-experimental design with a control and experimental group was employed. The sample consisted of 40 students of Teacher Education of Early Childhood Education. Both classes studied English for Early Childhood Education. Sample in the experimental group was treated by digital storytelling based on multimodal elements and local contents. The control group studied the storytelling based on a conventional video. The instrument used ware speaking rubric, Likert-Scale questionnaires, and interview. Data analysis for students' speaking performance consisted of the inter-reliability test, normality test, homogeneity, test of linearity, and ANCOVA. The procedures of thematic analysis adopted inductive and deductive coding. The result of study shows that digital storytelling with multimodal elements effectively enhances EFL learners speaking performance. The descriptive statistics show that students in the experimental group (M=85.4) significantly outperformed the control group (M=76.9) on their speaking performance by digital storytelling. The students perceived a positive perception of digital storytelling based on multimodal elements in learning English in terms of enjoyment of multimodal features such as visual and auditory and values depicted from local values. The study also explored several perceived obstacles in using digital storytelling in speaking, such as digital and technical literacy, language skill, creativity and innovative thinking, and collaborative learning.